Upaya Guru dalam Pengembangan Materi Ajar Pendidikan Agama Islam untuk Meningkatan Keaktifan Siswa SD Negeri 004 Cemaga Selatan - Anizar, Anizar; Hasmiza, Hasmiza; Syahroni, Said Ali (Mandalika Institute, 2025)
Islamic Religious Education (IRE) plays a strategic role in shaping students' character. However, the reality shows a low level of student engagement in IRE learning, often caused by conventional teaching methods and less relevant learning materials. This study aims to analyze the efforts of IRE teachers at Sekolah Dasar Negeri (Public Elementary School) 004 Cemaga Selatan in developing teaching materials to enhance student engagement. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Data analysis was conducted through the stages of reduction, data presentation, and conclusion drawing, with triangulation techniques used to ensure data validity. The results of the study reveal that the teacher implemented three main strategies: integration of local and contextual values, utilization of digital and interactive learning media, and the application of scientific and project-based approaches. These strategies have proven effective in increasing students’ active participation in discussions, group assignments, and hands-on activities. Learning became more enjoyable, relevant, and meaningful. The findings affirm that innovation in the development of teaching materials—adapted to students' needs and environments—can significantly improve both student engagement and the quality of IRE instruction. The study recommends strengthening support for teachers in developing contextual, creative, and digitally-based learning methods.